FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2013). - Yusuf Raihan; Kamaliah '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of the company's financial condition, return on assets, leverage ratio, the previous year's audit opinion, to the administration of going concern audit opinion.The sample used in this study are manufacturing companies listed on the Stock Exchange 2011-2013. The total sample in this study using purposive sampling of 130 companies based on a sample selection criteria that companies listed on the stock exchanges of Indonesia for 2011-2013, the presentation of the financial statements at the exchange rate (USD), and having problems financial difficulties, marked by profit conditions surgery during the study period the negative of the company has experienced a net loss in 2011-2013. Data were analyzed using logistic regression (logistic regression) with the help of a computer program SPSS version 17.0.The results showed that the company's financial condition, return on assets, leverage ratio, the previous year's audit opinion, have a significant effect on the provision of going concern audit opinion.Keywords : audit going concern, the company’s financial condition, return on asset, laverage ratio, the previous year’s audit opinion.